(Implementation of the Independent Learning Curriculum at SMA Negeri 2 Mataram, West Nusa Tenggara) - Maruf, Maruf; Emawati, Emawati; Ramdhani, Deddy (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this research is to determine the implementation of the Independent Curriculum in Islamic Learning. The object of study is the Islamic Religious Education Teacher at SMA Negeri 2 Mataram. Type of qualitative research, data collection techniques using observation and interviews. The research results showed that in implementing the Independent Learning Curriculum there were three stages carried out by teachers, namely the planning stage, implementation stage and evaluation stage. All these stages have been carried out by the teacher.